Application of Near-Infrared Spectroscopy for the identification of rock mineralogy from Kos Island, Aegean Sea, Greece - Kokkaliari, Maria; Iliopoulos, Ioannis (Bulletin of the Geological Society of Greece, 2020)
Near-Infrared spectroscopy (NIR) is a useful tool for direct and on-site identification of rock mineralogy in spite of the difficulties arising in spectral evaluation, due to limited availability of spectral libraries at the time. Especially in the field, a functional methodology for the identification and evaluation if possible, of the geologic materials, is of interest to many researchers. However, several different parameters (such as grain size, color, mineralogy, texture, water content etc.) can affect the spectroscopic properties of the samples resulting in spectral variability. The subject of the present work focuses in various lithotypes (monzodiorite, diorite, altered diorite, actinolite schist, cataclasite, slate) from Kos Island, Aegean Sea, in Greece, all bearing hydrous minerals in various amounts. The evaluation of the results obtained from NIR spectroscopy offered important qualitative information about the mineralogy of the lithotypes examined. The important asset of the method is that no sample preparation was necessary. From the reflectance spectra, the NIR-active minerals that were identified include chlorite, micas, amphiboles and epidotes. Petrographic and mineralogic analyses were also employed in order to confirm the NIR results and provide more detailed information about the mineralogy of the samples, the grain size and the orientation of the minerals. Correlation of wavelength positions at ~1400 nm with loss on ignition (LOI) values led us to relate the various lithotypes in terms of their petrological affinities. NIR spectroscopy was proved to be a useful tool, especially for the mineralogic identification of rocks underwent low- to medium grade metamorphism, from greenschist to amphibolite facies.